Sistem Pakar Diagnosa Sikap dan Gaya Belajar untuk Menerapkan Akhlakul Karimah pada Siswa - Kadrahman, Kadrahman; Sumijan, Sumijan; Yunus, Yuhandri (Jurnal Sistim Informasi dan Teknologi, 2020)
Expert system is one of the use of technology in supporting every human activity. One of the uses of the expert system is for education. The expert system will help teachers to analyze the attitudes displayed by students. The purpose of this study is to analyze the attitudes and learning styles of students, apply good moral methods to students and determine the type of good approach to students using the Forward chaining method. The data needed for this research is student attitude data, data on learning style types, and moral data of morality and data on solutions to the application of morality and character. This research resulted in a solution in the form of the method of moral lighting according to the learning style with data accuracy of 86.2%. The conclusion of this study is that the design of an expert system for diagnosing student attitudes makes it easier for teachers to approach students.